Signal to noise ratio enhancement using empirical wavelet transform - Lee, W.Y. (International Petroleum Technology Conference (IPTC), 2019)
Noise is the unwanted energy in a seismic trace opposed to the signals corresponding to reflected energy from the subsurface features. Since it can overlap with the main signals' energy and conceal the geological information, noise attenuation is one of the most important steps in seismic data processing. The most common method is frequency filtering. However, due to its limitations on separating the noise from signals, this method usually results in hurting the signal. Hence, it is important to develop an alternative method that can attenuate the noise without affecting the signal. Filters based on time-frequency analysis of the data can have a better separation of the noise from signal as they maintain the time localization of events while presenting their frequency content simultaneously. One of the recent approaches to time-frequency analysis of signals is the Empirical Wavelet Transform (EWT) which provides adaptive wavelet filter bank for signal analysis. In this paper, a filter is designed based on EWT for random noise attenuation and is applied on both synthetic and real data. To evaluate the proposed filter performance, its results are compared with the filters based on Short Time Fourier Transform and Wavelet transform. As the EWT filter separate different seismic features using the adaptive basis wavelets, it can attenuate the noise while preserving the signals with higher precision. Â© 2019, International Petroleum Technology Conference